Robust fixed-time control for DC-DC converter with matched and mismatched perturbations - Cholahan, Varin; Tangsrirat, Worapong (My University, 2025)
This paper introduces a state-dependent variable exponent coefficient for fixed-time sliding mode control. The proposed state-dependent sliding surface ensures system stability and facilitates a rapid response within a fixed timeframe, while also addressing both matched and mismatched perturbations. This sliding mode control is applied to the DC-DC converter, a system that frequently encounters mismatched issues. By using the fixed-time concept, the designed sliding mode surface exhibits robustness, enabling it to manage both matched and mismatched perturbations within a fixed-time duration. We first present the average mathematical model for the continuous mode DC-DC converter. Next, a state-dependent sliding surface with a variable exponent coefficient is developed. Following next, the controller is designed to regulate the converter's voltage while effectively rejecting both matched and mismatched disturbances. The stability of the proposed approach is evaluated through the use of a Lyapunov function. Lastly, numerical simulations demonstrate rapid convergence and significant robustness against uncertainties in parameters, both matched and mismatched. When compared to other fixed-time and finite-time schemes, the proposed fixed-time controller is notable for its high efficiency and relatively straightforward control solution.
Keywords: DC-DC converter; fixed-time control; mismatched parameter; nonlinear control; sliding mode control; state-dependent sliding surface